Igneous crystallisation, high pressure metamorphism and subsequent tectonic exhumation of the Jijal and Kamila complexes, Kohistan - Gough, S; Searle, M; Waters, D; Khan, M (2001)
The Jijal and Kamila complexes lie at the base of the Kohistan palaeo-island arc in northern Pakistan (Bard, 1983). It can be demonstrated that the Jijal complex originally crystallised from deep-seated subduction-related melts to form a basal arc ultramafic-mafic magma chamber, with primary igneous garnet being crystallised only near the base of the mafic portion of the chamber. An element of magma mixing also occurred at near-solidus temperatures, resulting in the crystallisation of small pockets of a silica-poor, hydrous magma within and immediately beneath the main gabbroic complex. Subsequent arc thickening (Yamamoto, 1993) with a subduction-related component imposed a high-pressure garnet granulite facies metamorphic overprint on the entire Jijal complex, with maximum equilibrium pressures and temperatures obtained from THERMOCALC being in excess of 14 kbar and 850°C in the mafic rocks. Metamorphic modelling of the complex using pseudosections, combined with relative thermobarometry of representative samples collected from throughout the entire complex, can further constrain the nature of this post-crystallisation metamorphic event. Later hydration of the upper parts of the Jijal complex and the lower parts of the Kamila complex, facilitated mainly by ductile shearing at lower pressures and temperatures than the initial metamorphism, resulted in the removal of garnet and clinopyroxene from the metamorphic assemblage, although this metamorphic re-equilibration did not occur at lower levels of the Jijal complex. Eventual exhumation of the Jijal and Kamila units can be shown to have been achieved by a combination of erosion and brittle faulting within the complex, and by reactivation of the MMT as an extensional structure at the base of the complex. Investigation of retrograde metamorphic overprinting (Ringuette et al., 1999) of some of the initial granulite facies assemblages can provide constraints on the final exhumation path of the Jijal and Kamila complexes.